'Risk of sexual violence against women and girls' in the construction of 'gender-neutral toilets': a discourse analysis of comments on YouTube videos. (1st October 2020) - Colliver, Ben; Coyle, Adrian
Abstract : This article considers how the risk of sexual violence against women and girls is topicalised in social media interaction about 'gender-neutral toilets'. In particular, it examines how versions of the category of 'transgender people' are assigned a key role within the construction of sexual violence risk. A discursive analysis is presented of 1, 756 online comments in response to ten YouTube videos relating to gender-neutral toilets. The analysis focuses on one theme entitled 'Gender-neutral toilets as a site of sexual danger' and its constituent sub-themes. The phenomenon of gender-neutral toilets was responded to with a limited set of gendered tropes that constructed and positioned stakeholders in culturally recognisable ways. Women and children were constructed as vulnerable to sexual violence, at risk from men (including versions of 'transgender women') and in need of protection. This transformed a debate over public space into a question of morality. The analysis contributes to existing literature by focusing on the discursive features involved in the construction of risk, and the implications of these constructions in minimising the need to address social structures that position transgender people as legitimate targets of violence.